Model Perancangan Sistem Informasi Akuntansi Budidaya Perikanan Berbasis SAK EMKM dan Android - S Supriyati; Dicky Muhamad Rizky (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2018)
The times when this is so rapid that we should always follow developments there. Moreover many systems of information circulating out there. But still many employers who have both information system for help in the recording in the operations. With these researchers are trying to make an information system based on android in the field of fisheries that will help entrepreneurs in the future. The research design was used in the survey is the design. This type of research is used in is basic research. This type of data is used in applicable data kualiatif. Types of research designs used in this research is descriptive-analistis. This research method used in survey methods, methods apply descriptive and exploratory methods. This data gathering techniques used in is observation and interview techniques. Model of development of the system that is used in is a waterfall. Development tools used in this system is to use the BPMN and diagrams use cases. This application is expected can help to manage every recording transactions that occurred in the business activities oprasional could make the books of financial something with the standards SAK EMKM.